Sequestering of pollutants from public market wastewater using Moringa oleifera and Cicer arietinum flocculants - Mohd,, Rosmawanie; Mohamed, Radin; Al-Gheethi, Adel; Pahazri, Fadzilla; Hashim, Amir; Mohd Zin, Shaylinda (ScienceDirect, 2018)
The present study aimed to investigate potential of Moringa oleifera and Cicer arietinum seeds for the treatment of public market wastewater in comparison to Alum and FeSO4. The flocculation process was assessed as a function of adsorbent dose (60–360 mg/L), pH (4 to 9) and mixing rate (50 to 300 rpm). The adsorption study was performed to find out the removal of biological oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS), oil and grease (O&G), colour, and turbidity in a lab-scale plant system (6 L). The results revealed that the use of M. oleifera resulted in the highest removal for BOD5, COD and O&G (68.08%, 79.1% and 83.3% respectively) at 180 mg/L, pH 7 to 8, and a mixing rate of 150 rpm. The use of Alum resulted in the highest removal percentage for TSS, colour and turbidity (87.17, 90.83 and 81.06% respectively) at 120 mg/L, pH 7 to 8, and a mixing rate of 150 rpm. The Langmuir adsorption isotherm was the best model for the removal of turbidity by M. oleifera and C. arietinum (R2 = 0.91 and 0.93) compared to the Freundlich model (R2 = 0.81 and 0.82). Moreover, the adsorption of COD (R2 = 0.91) by M. oleifera was fitted to both the Langmuir and Freundlich isotherms. In contrast, the Freundlich isotherm was the best for studying the removal of COD (R2 = 0.96) and O& G (R2 = 0.99) by C. arietinum. The findings obtained indicated that natural coagulants are applicable for improving the quality of public market wastewater.